Forest Management and the Water Cycle - Bredemeier, Michael (Springer, 2012)
The protective function of forests for water quality and water-related hazards, as well as adequate water supplies for forest ecosystems in Europe, are potentially at risk due to changing climate and changing land-management practices. Water budgets of forest ecosystems are heavily dependent on climate and forest structure. The latter is determined by the management measures applied in the forestry sector. Various developments of forest management strategies, imposed on a background of changing climate, are considered in assessing the overall future of forest–water interactions in Europe.